Internship Experience and Grit Shape Gen Z Work Readiness: Pengalaman Magang dan Ketekunan Membentuk Kesiapan Kerja Generasi Z - Intan Safitri; Luluk Fadliyanti; Nadia Nuril Ferdaus (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Work readiness is a central issue in human capital development, particularly in the context of Sustainable Development Goals and youth employment in emerging regions. Specific Background: In West Nusa Tenggara Province, open unemployment remains dominated by tertiary-educated graduates, indicating a mismatch between higher education outcomes and labor market demands among Generation Z fresh graduates. Knowledge Gap: Although prior studies have examined internship experience, work motivation, and grit separately, limited research has integrated these variables within a comprehensive model of work readiness grounded in Human Capital and Employability Capital theories. Aims: This study analyzes the relationships between internship experience, work motivation, and grit and their contribution to work readiness among 101 Gen Z fresh graduates using a quantitative survey and multiple linear regression. Results: The findings demonstrate that internship experience and grit have positive and statistically significant associations with work readiness, whereas work motivation does not show a significant partial relationship; collectively, the three variables significantly explain 53.3% of the variance in work readiness (R² = 0.533). Novelty: This study positions grit as the most dominant predictor within an integrated human capital framework combining experiential and psychological dimensions. Implications: The results underscore the importance of structured industry-relevant internship programs and the integration of grit-based character development in higher education curricula to strengthen graduate competitiveness in regional labor markets. Highlights: Practical workplace exposure shows a statistically significant positive association with graduate preparedness for employment. Psychological perseverance emerges as the strongest predictor within the regression model. The combined model accounts for 53.3% of variance in employment preparedness among respondents. Keywords: Gen Z, Grit, Work Readiness, Internship Experience, Work Motivation